Proportions of mechanical damages and their effect on post-harvest quality of avocado ‘Hass’ - Herrera González, Juan Antonio; Venegas González, Eulalio; Madrigal Huendo, Lucas (Revista Mexicana de Ciencias Agrícolas, 2017)
The avocado ‘Hass’ fruit is very susceptible to external and mechanical damages occurring in pre and post harvest. Harvesting and postharvest management can further reduce quality if it is not suitable. The present study aimed to estimate mechanical damages during pre-harvest and harvest, as well as its effect on postharvest. Mechanical damages were evaluated at different stages of harvesting and packing to estimate sample sizes suitable for inspection and evaluation of the aforementioned damages and their effect on post harvest quality of avocado ‘Hass’ for export. The harvester’s actions, during the harvesting process, have an effect on cuts (0.2-1.2%) and uneven (1-1.7%), as well as the transfer of the fruit inside the orchard (cuts 1.2%, bruises 2.02 %) and from this to the baler (bruises 4.57%). Some external damages (smallpox 30%, Trips 69% and clove 11%) remained constant at both harvest times, while others occurred in higher percentages in October (chickenpox, sunburn and bruising) than at the april harvests. Larger gauges are harvested in October (class I 31%, extra38% and super 23.4%) than in April (class i 23.4%, extra 32% and super 26.6%). The maximum sample size for evaluation and quality inspection was 374- 382 fruits per harvested lot.